1996
DOI: 10.2170/jjphysiol.46.485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrical Stimulation of the Central Amygdaloid Nucleus on the Nociceptive Neuron of the Cortex (SI) in the Cat.

Abstract: The effect of conditioning stimulation of the central amygdaloid nucleus (ACE) on the response of tooth pulp-driven (TPD) neurons in the first somatosensory cortex (SI) was investigated in cats anesthetized with N2O-O2 (2:1) and 0.5% halothane. The tooth pulp test stimulus was a single 30-450 microA rectangular pulse, and the conditioning stimuli of the ACE were trains of 33 pulses (300 microA) delivered at 330 Hz. The ACE conditioning stimulation markedly suppressed the response of the slow-type neurons with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The previous study has confirmed that brief electrical stimulation applied to the CeA evokes antinociception in the rat and cat. 54 Consequently we postulate that disinhibition in GABA CeA (caused by decreased level of D2 receptor) may facilitate analgesic (pain relief) and anxiolytic effects in incised mice. It seemed that analgesia might be mediated by decreased D2 receptor expressing and activation of CeA inhibitory neurons in the CeA in our study.…”
Section: Discussionmentioning
confidence: 97%
“…The previous study has confirmed that brief electrical stimulation applied to the CeA evokes antinociception in the rat and cat. 54 Consequently we postulate that disinhibition in GABA CeA (caused by decreased level of D2 receptor) may facilitate analgesic (pain relief) and anxiolytic effects in incised mice. It seemed that analgesia might be mediated by decreased D2 receptor expressing and activation of CeA inhibitory neurons in the CeA in our study.…”
Section: Discussionmentioning
confidence: 97%
“…An early study in guinea pigs showed that electrical stimulation of the amygdala may be algesic or analgesic, depending on the subregion stimulated (Lico et al, 1974). More recently, studies showed that electrical stimulation of the amygdala resulted in a reduction in nociception induced by formalin in rats (Mena et al, 1995) and a reduction in nociception during tooth pulp stimulation in cats (Kawarada et al, 1996). Electrical stimulation of the amygdala has also been demonstrated to enhance the startle reflex to an acoustic tone in rats (Rosen and Davis, 1990).…”
Section: Amygdalamentioning
confidence: 99%
“…The present report is the first to offer electrophysiological evidence that the amygdala exerts profound inhibition on nociception. A brief preliminary report of these findings has been presented previously [10].…”
mentioning
confidence: 91%